Post a New Question


posted by on .

This problem has been very hard for me. I would appreciate it if someone could maybe help..

Solve: 2a - b = ac + 3b for a

I came up with a = c + 4b but I really don't know..

  • Algebra - ,

    2a - b = ac + 3b
    to get a, first we need to transpose all terms containing a to one side of equation, and all other terms to the other side,, in this case the terms containing a are 2a and ac. let's just transpose them to the left side of equation,,
    since ac is on the right and we wish to transpose it to the left side, we change its sign from positive to negative:
    2a - b = ac + 3b
    2a - b - ac = 3b
    we do the same for -b. -b becomes +b if transposed to other side:
    2a - ac = 3b + b
    now we factor a from 2a - ac:
    a(2 - c) = 3b + b
    also, we can combine 3b and b:
    a(2-c) = 4b
    now to get a alone, we divide both side of equation by (2-c):
    a(2-c)/(2-c) = 4b/(2-c)
    a = 4b/(2-c)

    hope this helps~ :)

  • Algebra - ,

    Oh, wow, this does help! Fast response and detailed explanation.

    Thank you so much, appreciate it.
    Have a good one!

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question